BIOSORPTION OF METAL IONS Pb(II), Cu(II), AND Cd(II) ON Sargassum duplicatum IMMOBILIZED SILICA GEL MATRIX - Buhani Buhani; Suharso Suharso; Zipora Sembiring (Indonesian Journal of Chemistry, 2006)
Sargassum duplicatum algae biomass is biological material which has a potency to be used as a biosorbent adsorb metal ions from industrial liquid waste, because it has effective functional group as a ligand. However, the ability of the algae biomass in adsorbing of heavy metal ions has some problem such as; tiny size, low density, and easy to be degradated by other microorganism. In addition, algae biomass can not be used directly in adsorption column for its application as the biosorbent. In order to improve physical and chemical prpperties of algae biomass, it needs to be immobilized on silica gel matrix. Series of experiment have been done, morphology analysis of adsorbent surface was performed by using Scanning Electron Microscopy (SEM) and adsorption process to examine the effectiveness of algae biomass immobilized in adsorbing Pb(II), Cu(II), and Cd(II) was performed using batch method at 27 °C. Concentration of metal was determined by using Atomic Absorption Spectrophotometer (AAS) and identification of functional group was conducted using Spectrophotometer Infrared (IR). Data obtained showed that interacting among metal ions with algae biomass is optimum at a range of 60 minutes. Adsorption energies of metal ions resulted from the interaction of metal ions with the functional group of -C=O group from carboxyl and amide on algae biomass and -Si-OH group from silica were at a range of 21.09-25.05 kJ/mole.